2007
DOI: 10.1159/000109272
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Evaluation of AcrySof ReSTOR Multifocal Intraocular Lens for Treatment of Cataract

Abstract: Purpose: To evaluate the efficacy, safety and early visual quality of the AcrySof ReSTOR multifocal intraocular lens (IOL) following cataract surgery. Setting: Eye Center of Shandong University of Traditional Chinese Medicine, Jinan Shierming Eye Hospital, Jinan, Shandong, China. Methods:After small-incision phacoemulsification, AcrySof ReSTOR IOLs were implanted in 20 subjects (40 eyes, ReSTOR group). Monofocal IOLs were implanted in 18 subjects (36 eyes, control group). Three to six months following bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…In this study, the subjective near visual acuity of the ReSTOR group was better than that of the IQ group like in another study [1][2][3][4][5][6]. However, we could not prove this with objective tools such as OQAS.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In this study, the subjective near visual acuity of the ReSTOR group was better than that of the IQ group like in another study [1][2][3][4][5][6]. However, we could not prove this with objective tools such as OQAS.…”
Section: Discussioncontrasting
confidence: 70%
“…Several studies have evaluated the multifocal function of the ReSTOR by measuring the distance visual acuity and near visual acuity of patients who had cataract surgery with implantation of the lens. [1][2][3][4][5][6] However, they have a weakness in that they depend on the subjective visual acuity of the patients. Recently, Kim et al reported on the testing of the multifocal function of multifocal IOLs including ReSTOR using an optical bench system [7].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty studies were included in the meta-analysis,1938 of which 16 were prospective studies (80%) and four were retrospective (Table 1). Eight (50%) of the prospective studies were randomized.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, 1 study showed that the visual field detected with the Octopus 101 autoperimeter was not statistically different between patients with Acrysof Restor multifocal IOLs and monofocal IOLs. 2 Another study, however, demonstrated that as spot intensity and size during visual field testing were decreased, patients with multifocal IOLs experienced a greater decrease in visual field than in phakic patients and those with monofocal IOLs. 3 This may be consistent with the degradation of image quality seen through multifocal IOLs due to reduced contrast sensitivity.…”
Section: Discussionmentioning
confidence: 98%